2016
DOI: 10.1007/s10509-016-2755-7
|View full text |Cite
|
Sign up to set email alerts
|

The mode switching of PSR B2020+28

Abstract: This paper reports on polarimetric radiation properties based on the switching modes of normal PSR B2020+28 by analysing the data acquired from the Nanshan 25-m radio telescope at 1556 MHz. With nearly 8 hours quasi-continuous observation, the data presented some striking and updated phenomena. The change of relative intensity between the leading and trailing components is the predominant feature of mode switching. The intensity ratio between the leading and trailing components are measured for the individual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…We had also tried to search for GPs in our data at three frequencies. However, after correction for scintillation effects (Wen et al 2016), we failed to find any bright pulses with an energy larger than 10 times the average pulse energy.…”
Section: Discussionmentioning
confidence: 70%
“…We had also tried to search for GPs in our data at three frequencies. However, after correction for scintillation effects (Wen et al 2016), we failed to find any bright pulses with an energy larger than 10 times the average pulse energy.…”
Section: Discussionmentioning
confidence: 70%
“…They showed that the energy distribution for the majority of the pulsars could be well described by a lognormal distribution. In addition, the study of the energy distribution from the mode-changing and nulling pulsars revealed that they exhibit multiple energy states (Wen et al 2016a(Wen et al , 2020. The energy distributions of giant pulses, which follow a power-law distribution, suggest that the giant pulse phenomenon is distinct from the regular pulsar radio emission (Chen et al 2020;Wen et al 2021).…”
Section: Pulse Energy Distributionmentioning
confidence: 99%
“…The data from each frequency channel were folded at the apparent pulsar period to form subintegrations of typical duration around 1 minute. The calibrated observations were provided by a digital filterbank system (DFB) with a frequency resolution of 0.5 MHz, or 1024 channels across the full band (Wen et al 2016a). The full-Stokes spectra were acquired in a 512 MHz bandwidth centered at 1556 MHz radio frequency.…”
Section: Observations and Data Reductionmentioning
confidence: 99%